PENERAPAN DINAMIKA KELOMPOK SOSIAL DALAM MENURUNKAN INFEKSI KECACINGAN DAN MENINGKATKAN STATUS GIZI, PERKEMBANGAN ANAK TODDLER DI KOTA KEDIRI - Elfi Quyumi Rahmawati; Erna Susilowati (coba, 2019)
ABSTRACT Worm infections in the digestive tract cause the process of absorption of nutrients disturbed. Low nutritional status results in a decrease in children's cognitive abilities so that the development of children experience delays. Toddler children are the group most at risk of the occurrence of worm infections. Children with helminthiasis have low albumin and total protein, diarrhea and anemia arise, thereby reducing learning achievement and productivity. Family assistance needs to be done by providing knowledge and practice on how to prevent worm infections in the form of counseling about clean and healthy living behavior, counseling about the importance of fulfilling balanced nutrition in children. The purpose of this study was to determine the effect of social group dynamics on helminthiasis infection, nutritional status and development of toddler age children. This research is a pre-experimental study with a one group pre-post test design design in families with toddler-age children in the village of Lirboyo Kediri. Worm data in children was obtained by taking stool samples and examined by the formal ether concentration method in the parasitology laboratory, nutritional status data obtained by measuring body weight and age. Child development data is obtained by DDST measurement (Denver Devalment Screning Test). Data analysis using bivariate analysis, namely chi square test and multivariate analysis using the Wilcoxon test with a confidence level of 95% (α = 0.05). The results of this study found an improvement in Toddler nutritional status (P = 0,000), there was an increase in toddler development (p = 0,000 ), With the social group dynamics expected to detect early worm infections, treatment and improvement of children's nutritional status can be done so that the delay in child development can be prevented.